Diet Bubuk Cangkang Anadara Granosa dan Susu Kedelai Meningkatkan Kekerasan Permukaan Gigi - Rima Parwati Sari; Syamsulina Revianti; Puguh Bayu Prabowo (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Wistar teeth always be growth, but to remodeling needed some minerals and protein to accelerate enamel and dentin to be hardness. Anadara granosa cockle shell showed that it contains a lot of minerals, majority calcium that is important to mineralized of teeth. In the absorption of calcium need amino acid as protein-binding transporter that found in soya milk. The aim of this study was to proved diet combination Anadara granosa cockle shell powder and soya milk increased surface hardness wistar teeth. Twenty eight (28) wistar rats were divided four groups. 1st group was given aquadest, 2nd (Anadara granosa cockle shell powder 0,1368 mg/grBB), 3rd (soya milk 0,015 ml/grBB), 4th (Anadara granosa cockle shell powder 0,1368 mg/grBB and soya milk 0,015 ml/grBB). On 12nd day tooth incisors sample was extracted and done measurement by microhardness vickers. All of datas in this study were analyzed by ANOVA and LSD (p=0,05). This study showed that there was significant difference (p>0.05) between 2nd and 4th group with 1st and 3rd groups so it can be cancluded that the use of diet combination Anadara granosa cockles shell powder and soya milk can increased surface hardness of wistar teeth.